Synthesis and characterization of novel dimeric ionic liquids by conventional approaches. - Ganesan, Kilivelu; Alias, Yatimah (MDPI, 2008)
The (1)H-NMR shifts of the imidazolium protons of some novel dimeric ionic liquids were examined in various deuterated solvents. Interactions between the solvent and the imidazolium salt of butyl substituted ionic liquids were observed to give higher chemical shifts than methyl substitution.